Liquidity as a Moderator of Profit Growth Determinants in Village Credit Institutions: An Empirical Analysis - Sugiartha, I Gede Ferry; Atmadja, Anantawikrama Tungga; Musmini, Lucy Sri (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
This study investigates the influence of net profit margin and capital adequacy on profit growth, with liquidity serving as a moderating variable, in Village Credit Institutions (LPDs) in Badung Regency. The research population comprised 122 LPDs registered with the LPLPD in Badung Regency. Using a purposive sampling method, 109 LPDs were selected, resulting in a total of 654 observations over a six-year period from 2019 to 2024. Data analysis was conducted using the Moderated Regression Analysis technique. The findings indicate that both net profit margin and capital adequacy exert a positive effect on profit growth. Additionally, liquidity was found to strengthen the relationship between these variables and profit growth, confirming its moderating role. This implication proves that the right LPD utilizes liquidity for optimal quality credit expansion, so that net income margins and capital assessments have a positive impact on profit growth. Keywords: Liquidity; Net Profit Margin; Capital Assessment; Profit Growth